An r package and online resource for macroevolutionary studies using the ray‐finned fish tree of life. Issue 7 (22nd April 2019) - Chang, Jonathan; Rabosky, Daniel L.; Smith, Stephen A.; Alfaro, Michael E.
Abstract: Comprehensive, time‐scaled phylogenies provide a critical resource for many questions in ecology, evolution and biodiversity. Methodological advances have increased the breadth of taxonomic coverage in phylogenetic data; however, accessing and reusing these data remain challenging. We introduce the Fish Tree of Life website and associated r package fishtree to provide convenient access to sequences, phylogenies, fossil calibrations and diversification rate estimates for the most diverse group of vertebrate organisms, the ray‐finned fishes. The Fish Tree of Life website presents subsets and visual summaries of phylogenetic and comparative data, and is complemented by the r package, which provides flexible programmatic access to the same underlying data source for advanced users wishing to extend or reanalyse the data. We demonstrate functionality with an overview of the website, and show three examples of advanced usage through the r package. First, we test for the presence of long branch attraction artefacts across the fish tree of life. The second example examines the effects of habitat on diversification rate in the pufferfishes. The final example demonstrates how a community phylogenetic analysis could be conducted with the package. This resource makes a large comparative vertebrate dataset easily accessible via the website, while the r package enables the rapid reuse and reproducibility of research results via its ability to easily integrate with other r packages and software for molecular biology and comparative methods.